BIONICS AS TECHNOGENIC MODIFICATION OF CO-EVOLUTIONAL DYNAMICS - A. I. Lojko; E. B. Yakimovich (Наука и техника)
The paper investigates a bionics phenomena and those possibilities which are opened in the interdisciplinary field with the purpose to solve problems of co-evolutional methodology.